Pengaruh Floor Display dan Promosi Buy One Get One terhadap Impulse Buying serta Kepuasan Pelanggan pada Produk JNC Cookies - Imas Juliah; Theresia Militiana; Rusmadi Wongso (Commodities, Journal of Economic and Business, 2026)
This study aims to analyze the impact of visual merchandising and promotional strategies on impulse buying behavior and customer satisfaction in the retail context. The findings reveal that Floor Display (X1) and Buy 1 Get 1 Promotion (X2) have a positive and significant effect on Impulse Buying (Y1) and Customer Satisfaction (Y2). Furthermore, Impulse Buying acts as a mediating variable that strengthens the relationship between marketing strategies and customer satisfaction. An R-square value of 0.786 indicates that the model explains 78.6% of the variation in customer satisfaction. These results highlight the importance of attractive visual design, strategic promotions, and enjoyable, ethical shopping experiences in sustaining customer satisfaction.